Assessing the Technological and Nutritional Functionality of Curd Cheese in the Overall Gluten-Free Bread Quality - Graça, Carla; Raymundo, Anabela; Sousa , Isabel (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
Replacing wheat flour in the breadmaking process is a technology challenge since the absence of gluten has a strong influence on overall bread quality. Protein-rich source substitutes are often used to aid a formation of a protein network capable of mimicking gluten-like structure so that it would support the gas cells of the dough foaming. Apart from the protein structuring ability, the interaction with starch granules can perhaps be useful to make them less available for enzymatic degradation, becoming a nutritional advantage. When the bread matrix includes simultaneously proteins and lipids, the nutritional advantages can be further enhanced, since the lipids can form lipid-amylose complexes influencing the final dough consistency. Therefore, nutritional gains in terms of the glycemic response of gluten-free bread can be positively improved. This study aimed at evaluating the technological and nutritional functionality of curd cheese as a protein and lipid source, and as a promising alternative bakery ingredient in gluten-free breadmaking. The influence of curd cheese, based on its ability to strengthen gluten-free dough structure, by testing several levels of addition (5% up to 20%, weight/ weight) focused on: i) dough rheology properties, mainly flow and viscoelastic profile modifications, ii) starch physical behaviour by pasting properties measurements, was assessed in detail. The quality of the derived bread samples was evaluated by measuring the post-baking quality. Nutritional gains focused on the chemical composition and glycemic response were further assessed. Considering the highest level of curd cheese (20%) tested, improvements in bread quality were observed, leading to a considerable increase in bread volume (73%) and softness (65%), with a marked reduction in staling kinetic (70%), comparing with control bread. Additionally, an improvement in nutritional value in terms of proteins (80%) and minerals content, particularly P, Mg and Ca, covering more than 15% of the daily recommended doses, was obtained. As for the glycemic response, a considerable reduction of 40%, resulting in bread with an intermediate glycemic index, was achieved. Strong linear correlations (R2 > 0.902) were observed between dough rheology properties and bread quality attributes, pasting properties, in vitro starch digestibility, and glycemic index. The linear relations found can be used to support the hypothesis that the curd cheese addition had a markedly influence on the overall bread quality and nutritional value.